The Recycle of Hotel X Lembang Domestic Liquid Waste : A Form of Fulfilling Environmental Legal Obligations - Nurhasanah Nurhasanah; Imam Rozal Fathar; A. Hadian Pratama Hamzah; Husni Syawali (Faculty of Law, Universitas Pekalongan, 2022)
In hotel activities, liquid waste is generated from bathrooms, toilets, laundry, and kitchen activities. From the hotel's activities, wastewater is classified as domestic liquid waste. Efforts to treat waste that are comprehensive and sustainable are continuously needed as part of the fulfillment of environmental legal obligations that have been regulated in PP NO.2 the YEAR 2021 concerning environmental management. The purpose of this research is to know how to protect water management, air management, and land management. Moreover, knowing the quality of the results of the domestic liquid waste recycling process at Hotel X Lembang using the Indonesian Government Regulation approach and the LHK Ministerial Regulation. This study used an empirical juridical approach through primary and secondary data and analyzed descriptively and qualitatively. Data collection techniques were carried out through laboratory test results of recycled water samples and literature studies. The wastewater quality test aims to determine the condition of the recycled water using ozone based on the established quality standards, namely by referring to PP RI No. 22/2021 Appendix VI class 4 according to its designation, and PerMen LHK RI No. P.68/2016 Appendix I Regarding Separate Domestic Wastewater Quality Standards. The parameter test results are by the quality standard according to the Regulation of the Minister of Environment and Forestry No. 68 of 2016, where H 6.96; TSS of 10 mg/l; ammonia 3.02 mg/l; oil/fat <0.94 mg/l; BOD5 19.8 mg/l; COD 63.8588 mg/l; total coliforms, 920 MPN/100 ml. Based on the results of research and discussion, it was concluded that the system for recycling domestic liquid waste at Hotel X Lembang using ozone met the appropriate quality standard ministerial Regulation of LHK RI No.P.68/2016 Attachment I and PP RI Number: 22/2021 Attachment VI, class 4 according to its designation. It is a manifestation of the fulfillment of environmental legal obligations.